Legal Protection Of The Owner Of The Legal Consequences Of The Onset Of Overlap - Aditia Karsa Ginting; Tetti Samosir (CV. AFDIFAL MAJU BERKAH, 2026)
Credential are issued to rights holders for the benefit of the rights holders, as clearly stipulated in Clause 30 Verse 1 and Clause 31 of the PPPT. Clause 32 Verse (1) retrieved the proof of land ownership is the Certificate. As long as the information contained in the certificate is correct and consistent with the measurements and land registry, the certificate is considered strong evidence. Clause 32 Verse 2 regulates that with regard to a plot of land, If a certificate is generated in the presence of an individual or legal entity and is achieved in good faith and with legitimate tenure over the land, then any other entity claiming ownership of the underlying land forfeits the legal right to pursue such claims if-within a time period of 5 (five) years from the time of certificate issuance, they have not filed a administrative objection in a written form to the entitled owner and tBPN or filed a dispute in court. The research method used is normative legal research. Normative legal research uses exemplary normative studies in the form of behavioural legislation, such as legislative review. Therefore, it focuses on the stockpile of laws, legal principles and doctrines, legal discovery in specific cases, legal theories, the degree of legal synchronisation, judicial comparisons, and legal historical studies. This Research utilises a case approach by assessing the relevant cases which have become final court decisions. Legal protection in the decision is in accordance with applicable Legislation, which are based on the provisions of agrarian law, namely Clause 19 UUPA and Clause 2 PPPT, 53 Verse 2 letter c Act Number 5 Year 1986 on Administrative Justice, and Clause 16 Act Number 4 Year 2004 on Judicial Power. Factors causing the overlap (overlapping) of certified land ownership is a change from a manual base map into a digital base map, at the time of transfer from the initial base map to a digital base map there are parts that are not entered/ lost, so that the BPN Medan city sees that the land has never been registered and other factors can also be caused by the presence of persons (land mafia) originating from the BPN itself and persons from outside the BPN to issue Rights on land objects that are also being processed certificates. So that when the certificate process is completed there are parties who are harmed by the emergence of two pedestal rights over the same object.